Unfounded Sexual Assault: Women's Experiences of Not Being Believed by the Police. Issue 11 (June 2022) - Murphy-Oikonen, Jodie; McQueen, Karen; Miller, Ainsley; Chambers, Lori; Hiebert, Alexa
One in four women will experience sexual assault in their lifetime. Although less than 5% of sexual assaults are reported to law enforcement, one in five cases reported to police are deemed baseless (by police) and therefore coded as "unfounded." Police officers are in a unique position to act as gatekeepers for justice in sexual assault cases, given their responsibility to investigate sexual assault reports. However, high rates of unfounded sexual assaults reveal that dismissing sexual violence has become common practice amongst the police. Much of the research on unfounded sexual assault is based on police perceptions of the sexual assault, as indicated in police reports. Women's perspectives about their experiences with police are not represented in research. This qualitative study explored women's experiences when their sexual assault report was disbelieved by the police. Data collection included open-ended and semi-structured interviews with 23 sexual assault survivors. Interviews covered four areas including the sexual assault, the experience with the police, the experience of not being believed, and the impact on their health and well-being. Interviews were audio-recorded, transcribed, and entered into NVIVO for analysis. Data were analyzed using Colaizzi's analytic method, resulting in the identification of four themes, including, (a) vulnerability, (b) drug and alcohol use during the assault, (c) police insensitivity, and (d) police process. The women in this study who experienced a sexual assault and reported the assault to police were hopeful that police would help them and justice would be served. Instead, these women were faced with insensitivity, blaming questions, lack of investigation, and lack of follow-up from the police, all of which contributed to not being believed by the institutions designed to protect them. The findings from this research demonstrate that police officers must gain a deeper understanding of trauma and sensitive communication with survivors of sexual assault.